EXPLORING THE USE OF MODAL AUXILIARY VERBS IN CORPUS OF CONTEMPORARY OF AMERICAN ENGLISH (COCA) - Meita Lukitawati Sujatna; Eva Tuckyta Sari Sujatna; Kasno Pamungkas (Sosiohumaniora, 2019)
ABSTRACT. This paper deals with the frequent use of modal auxiliary verbs in Corpus of Contemporary of American English (COCA). The modal auxiliary verbs mentioned as the data are can, could, will, would, may, might, shall, should, and must. Each data collected are taken from COCA in https://corpus.byu.edu/coca/. The research method is descriptive analysis; the present writers describe every data related to their function in each clause. The findings are related to the highest frequency and the number of elements follow the modal auxiliary verbs. From the 6,008,840 data, it is found the verb would (1,301,269 data) is the most frequently used, it is followed by the verb can (1,228,608 data), the verb will (1,118,515 data), the verb could (885,835 data), the verb may (494,144 data), the verb should (435,903 data), the verb might (300,258 data), the verb must (223,936 data), and the verb shall (20,372 data). This study has also revealed the number of elements following each of modal auxiliary verbs found in the COCA. It is reported that the verb would has seven different types,will has five different types, could and should has four different types, can, may, must, and shall have three different types, and might has two different types as the least number of elements following the verb. From the data analyzed, it is also reported that the modal auxiliary verb would is not only has the highest number in data (as the highest frequency) but also has various number of elements follow the verb.